The impact of USDA's business and industry loan guarantee program on tax revenue in Oklahoma communities. Issue 2 (15th March 2021) - Smith, Ty Rope; Whitacre, Brian E.
ABSTRACT: Many public-sector programs are focused on economic development in rural areas, but few are formally evaluated. One often-overlooked component of effective rural development is the generation of local sales tax revenue, which helps fund city amenities and services. This paper evaluates whether the United States Department of Agriculture's (USDA) Business and Industry (B&I) Loan Guarantee program impacted sales tax revenue for recipient Oklahoma communities. Sales tax revenue and demographic/business data for all Oklahoma communities that charged a sales tax between 2005 and 2015 are meshed with information on B&I loan recipients during that time. Coarsened exact matching (CEM) and multivariate regression techniques are then used to assess impacts on local sales tax revenues. The results demonstrate that the B&I program had a positive impact on total retail sales per capita over the full period, and that the effects were evident in recessionary but not expansionary periods. The evidence suggests that the B&I program can improve the financial health of recipient communities, and that their impacts are likely larger during economic downturns when tax revenue is even more vital for rural communities.